Effect of two desensitizing agents on dentin permeability in vitro - ISHIHATA, Hiroshi; KANEHIRA, Masafumi; FINGER, Werner J.; TAKAHASHI, Hidekazu; TOMITA, Makoto; SASAKI, Keiichi (Journal of Applied Oral Science, 2017)
Objective The aim of this in vitro study was to investigate the effect of two desensitizing agents and water on hydraulic conductance in human dentin. Material and Methods GLUMA Desensitizer PowerGel (GLU) contains glutaraldehyde (GA) and 2-hydroxyethyl methacrylate (HEMA), and Teethmate Desensitizer (TD) is a powder comprising tetracalcium phosphate (TTCP) and dicalcium phosphate anhydrous (DCPA) that is mixed with water. Deionized water was used as a negative control (CTR). Thirty discs with a thickness of 1.2 mm were cut from the coronal dentin of the third molars and cleaned with 0.5 M EDTA (pH 7.4). After being mounted in a split-chamber device, the discs were pressurized with water at 1 kPa and 3 kPa in order to measure flow rates with a highly sensitive micro-flow sensor and to calculate hydraulic conductance as a baseline value (BL). Following the application of GLU, TD, and CTR (n=10), hydraulic conductance was remeasured with intermittent storage in water after 15 min, 1 d, 1 w, and 1 m. Reduction in permeability (PR%) was calculated from hydraulic conductance. Data were statistically analyzed using nonparametric methods (α